On the applicability of the Stern-Geary relationship to determine instantaneous corrosion rates in macro-cell corrosion - Angst, U.; Büchler, M. (Materials and corrosion, 2015)
The well‐known Stern–Geary equation was derived on the basis of the theory by Wagner and Traud and relies on the so‐called mixed potential of an electrode subject to uniform corrosion. Nevertheless, it is common practice to apply the linear polarization method to determine instantaneous corrosion rates in situations of galvanic corrosion. In the present work, the applicability of the Stern–Geary equation to galvanic corrosion was in detail discussed both with help of theoretical considerations and experimental measurements. The primary reason why the application of the Stern–Geary equation to galvanic corrosion is fundamentally incorrect is the fact that a well‐defined mixed potential does for galvanic elements not exist. In this work, equations were derived that allow a correct calculation of the corrosion rate for galvanic cells. However, the required variables can, in usual practical situations, not be measured. Application of the Stern–Geary equation to galvanic cells is in the literature claimed (or assumed) to yield adequate results. An explanation for this apparent applicability was identified in the fact that two major errors have a compensating effect so that they tend to cancel each other out. The extent to which this is possible depends strongly on the actual conditions such as the geometry of the galvanic cell as well as on the position of the counter and the reference electrode (RE). Nevertheless, since this apparent applicability is owing to specific conditions rather than a fundamental applicability of the method, further research is clearly needed to characterize these conditions and their limits in detail.